AYAT-AYAT DO'A DALAM AL QUR'AN PRESPEKTIF MAKNA DASAR DAN RELASIONAL - Abdul Wahab Rosyidi, M.Pd (El-QUDWAH, 2007)
One of approaches in comprehending al Qur’an is semantic or meaning approach. There are three ways to goin the meaning; first is though microstructure, that is haw to meaning of the text can be made though the structural analysis of sentence and phrase. Second, stylistic, that is how the special stylistic of al Qur’an to be the tool to faind the meaning of the text. Third, semantic, that is how the choice of word or vocabulary used in al Qu’an has the basic meaning and the relational meaning. Do’a in the religion  language has many terms: do’a, dzikir, istighosah, riyadoh, and the essence of sholat which is done by a moslem every day has been also considered as do’a. One of the requirements to make the do’a “terkabul” one should understand  to meaning of the word form the language s/he uttered (linguistic phenomenan). And one of ways to find of word meaning is though semantic approach, the basic meaning and relational meaning. The research question one: how the basic meaning and the relational meaning of do’a in al Qur’an? Is the relational meaning always attached to the key word of do’a in al Qur’an. The focus of the researche is to explore the basic meaning and the important relational vocabulary which bicome the key word consisting do’a explicithy, that is the verse of do’a with the key word “fi’il madhi, and amar”, the research belongs library research though qualitative approach. After analyzing the key word of the verse of do’a in al Qur’an using basic of meaning and relational meaning prespective, the conclusion are: 1) the basic meaning of the key word in the verse of do’a in al Qur’an is lexical meaning of the words, while the relational meaning is the meaning produced by the texual and contextual, in this case the relational meaning of the verse of do’a; constitutes, synonym, antonym, ambiguity. 2) In the verse of do’a in al Qur’an, the relational meaning does not always attach to the key words; although it is related to the other words, it sametime still has lexical meaning.Kata Kunci: Ayat-ayat Al Qur'an, makna dasar, relasional